Implication of non-coding RNA-mediated ROCK1 regulation in various diseases - Ghafouri-Fard, Soudeh; Poornajaf, Yadollah; Hussen, Bashdar Mahmud; Abak, Atefe; Shoorei, Hamed; Taheri, Mohammad; Sharifi, Guive (Frontiers in Molecular Biosciences, 2022)
Rho Associated Coiled-Coil Containing Protein Kinase 1 (ROCK1) is a protein serine/threonine kinase which is activated upon binding with the GTP-bound form of Rho. This protein can modulate actin-myosin contraction and stability. Moreover, it has a crucial role in the regulation of cell polarity. Therefore, it participates in modulation of cell morphology, regulation of expression of genes, cell proliferation and differentiation, apoptotic processes as well as oncogenic processes. Recent studies have highlighted interactions between ROCK1 and several non-coding RNAs, namely microRNAs, circular RNAs and long non-coding RNAs. Such interactions can be a target of medications. In fact, it seems that the interactions are implicated in therapeutic response to several medications. In the current review, we aimed to explain the impact of these interactions in the pathoetiology of cancers as well as non-malignant disorders.